The effect of TikTok use on internet addiction of college students in Somalia: a cross-sectional study. - Gezginci Akpinar, Elif; Eker, Hasan Huseyin (International Journal of Environmental Health Research, 2025)
This study aimed to assess the effect of TikTok use on the internet addiction of college students in Somalia. This cross-sectional study was conducted with 210 students at the faculty of health sciences of a university in Mogadishu, Somalia. The data were obtained with the Individual Information Form and Young Internet Addiction Test-Short Form. The students' internet addiction average score was 31.93±7.14. A positive, very weak, significant correlation was determined between the students' daily time spent on TikTok and internet addiction (r=.190, p=.006). Internet addiction scores of students having a TikTok account and using the TikTok application were found to be significantly higher than students not having (p=.027) and not using the application (p=.032). This study shows that most students had a TikTok account and actively used this application, and their internet addiction level was moderate. The students having a TikTok account and using the application had higher internet addiction.